Опосредованная липосомами доставка ДНК в протопласты дрожжей Saccharomyces cerevisiae - Костецкий, И.Е.; Кордюм, В.А. (Биополимеры и клетка, 1987)
Изучена возможность трансформации протопластов дрожжей Saccharomyces cerevisiae с помощью ДНК плазмиды RB4, заключенной в липосомы. Установлено, что частота трансформации компетентных клеток дрожжей включенной в липосомы плазмидной ДНК в 8—12 раз выше, чем свободной ДНК. Показано также, что «пустые» липосомы стимулируют трансформацию протопластов S. cerevisiae плазмидной ДНК. Вивчено можливість трансформації протопластів дріжджів Saccharomyces cerevisiae за допомогою ДНК плазміди RB4, укладеної в ліпосоми. Встановлено, що частота трансформації компетентних клітин дріжджів включеної в ліпосоми плазмідної ДНК у 8–12 разів вища, ніж вільної ДНК. Показано також, що «порожні» ліпосоми стимулюють трансформацію протопластів S. cerevisiae плазмідної ДНК. To determine the peculiarities of plasmid DNA delivery by liposomes to yeast protoplasts (Saccharomyces cerevisiae) plasmid RB4 was encapsulated into large monolamellar liposomes from lecithin and cholesterin (mol, ratio 5:1). Fusion of liposomes with protoplasts was carried out. The uptake of plasmid DNA incorporated into liposomes by competent yeast cells was shown to exceed 8–12 fold than of free DNA. Liposomes without incorporated DNA were found to promote transformation of S. cerevisiae protoplasts 5–8 fold, if DNA concentration in a sample was 20–40 (μg/ml. The effect was absent at higher DNA concentrations in a sample (150–200 μg/ml).